Kesan penggunaan peta konsep dalam pemahaman teks - Belinda, Kathy Khoo @ Belinda ak Kija. (Universiti Malaysia Sarawak (UNIMAS), 2003)
This research was carried out to identify the effects ofconcept mapping to enhance text comprehension. Twenty-eight first year students ofcognitive Science course from Universiti Malaysia Sarawak (UNIMAS) participated in this research. This is an experimental research and the results ofthe pre-test and post-test compared using SPSS software. The results show that the achievement of experimental group is beller than the control group. This study also shows that concept mapping can enhance the understanding of text comprehension .